Investigation of AC loss of superconducting field coils in a double-stator superconducting flux modulation generator by using T-A formulation based finite element method. (13th April 2021) - Liu, Yingzhen; Ou, Jing; Cheng, Yi; Schreiner, Fabian; Zhang, Yuanzhi; Vargas-Llanos, Carlos; Grilli, Francesco; Qu, Ronghai; Doppelbauer, Martin; Noe, Mathias
Abstract: In order to reliably make use of superconductors in wind generators, a double-stator superconducting flux modulation generator is proposed here to avoid rotation of field coils and armature windings. The superconducting field coils are located in the inner stator while the armature windings are placed in the outer stator. In this way, the stationary-rotatory couplings of current and cryogenic coolants for superconducting field coils and/or armature windings are removed. Because of the modulation effect of the reluctance rotor between the two stators and the armature reaction field, moving AC magnetic fields are acted on superconducting coils in the inner stator. These moving AC magnetic fields are called magnetic field harmonics in the flux modulation generators. The frequencies of these harmonics are multiples of rotor mechanical frequency. Compared to synchronous superconducting generators, the amplitudes of the harmonics are higher. Even though methods to reduce the amplitudes of harmonics have been studied, the level of the AC loss in the superconducting field coils is still unknown. In this paper, numerical simulations based on the T – A formulation are used to estimate the AC loss of the superconducting field coils in a 10 MW double-stator superconducting flux modulation generator. It is found that by choosing a suitable working temperature, the AC loss of the superconducting field coils without any harmonic reduction methods is not very high, but eddy current loss of copper thermal shield inside the cryostat is significantly higher.